Antihypertensive Medication Nonpersistence and Low Adherence for Adults <65 Years Initiating Treatment in 2007–2014. Issue 1 (July 2019) - Tajeu, Gabriel S.; Kent, Shia T.; Huang, Lei; Bress, Adam P.; Cuffee, Yendelela; Halpern, Michael T.; Kronish, Ian M.; Krousel-Wood, Marie; Mefford, Matthew T.; Shimbo, Daichi; Muntner, Paul
Abstract : Previous evidence suggests modest improvements in antihypertensive medication adherence occurred from 2007 to 2012 among US adults ≥65 years of age. Whether adherence improved over time among adults <65 years of age is unknown. We assessed trends in antihypertensive medication nonpersistence and low adherence among 379 658 commercially insured adults <65 years of age initiating treatment in 2007–2014 using MarketScan claims. Nonpersistence was defined as having no days of medication available to take during the final 90 days of the 365 days following initiation. Among beneficiaries who were persistent to treatment, low adherence was defined by having antihypertensive medication available to take for <80% of the days in the 365 days following initiation (ie, proportion of days covered <80%). In 2007 and 2014, 23.3% and 23.5% of patients were nonpersistent to treatment, respectively, and 42.3% and 40.2% had low adherence, respectively. The relative risks for nonpersistence and low adherence were lower among beneficiaries initiating treatment with an angiotensin-converting enzyme inhibitor (0.95; 95% CI, 0.94–0.97 and 0.97; 95% CI, 0.96–0.98, respectively), angiotensin receptor blocker (0.86; 95% CI, 0.85–0.88 and 0.99; 95% CI, 0.97–1.00, respectively), or multiclass regimen (0.82; 95% CI, 0.80–0.84 and 0.88; 95% CI, 0.86–0.89, respectively), prescribed 90-day versus 30-day prescriptions (0.67; 95% CI, 0.66–0.68 and 0.70; 95% CI, 0.69–0.71, respectively), or who received medications by mail versus at the pharmacy (0.93; 95% CI, 0.90–0.95 and 0.90; 95% CI, 0.88–0.92, respectively). In conclusion, several modifiable factors were associated with lower rates of both antihypertensive medication nonpersistence and low adherence among adults <65 years of age initiating treatment in 2007–2014. Abstract : Supplemental Digital Content is available in the text.